The naturalized flora of Brazil: a step towards identifying future invasive non-native species - Zenni,Rafael Dudeque (2015)
Abstract Human-mediated species introductions are one of the defining factors of the Anthropocene. Non-native species can form invasive populations that affect biodiversity, ecosystem services, or farming. Here I summarized data on naturalized vascular species from the Brazilian list of seed plants and tested the hypotheses that more populated regions and biomes with less remaining natural vegetation harbor more naturalized species. The Atlantic Forest had the largest number of naturalized species, whereas the Pampa had the highest proportion of naturalized species in relation to the biome's total richness. The number of naturalized species was affected both by human population size and proportion of remaining natural vegetation. Family Poaceae had the highest numbers of naturalized species in all biomes, and, together with Asteraceae and Fabaceae, forms the top three families in number of naturalized species in five of the biomes. There were no records of species naturalized in all six biomes. However, of the 46 species naturalized in five out of six biomes, half were Poaceae. The results indicate that the Brazilian flora is currently composed both by native and naturalized species. Assessments of invasion risks and of impacts by naturalized species could help set management priorities and resource allocation towards control.